Energy Partition at Collisionless Supercritical Quasi‐Perpendicular Shocks. Issue 10 (13th October 2022) - Schwartz, Steven J.; Goodrich, Katherine A.; Wilson, Lynn B.; Turner, Drew L.; Trattner, Karlheinz J.; Kucharek, Harald; Gingell, Imogen; Fuselier, Stephen A.; Cohen, Ian J.; Madanian, Hadi; Ergun, Robert E.; Gershman, Daniel J.; et al.
Abstract: Collisionless shocks in astrophysical plasmas are important thermalizers, converting some of the incident flow energy into thermal energy, and non‐thermalizers, partitioning that energy in unequal ways to different particle species, subpopulations thereof, and field components. This partition problem, or equivalently the shock equation of state, lies at the heart of shock physics. Here, we employ systematically a framework to capture all the incident and downstream energy fluxes at two example traversals of the Earth's bow shock by the Magnetospheric Multiscale Mission. Here and traditionally, such data has to be augmented by information from other spacecraft, for example, to provide more accurate measurements of the cold solar wind beam. With some care and fortuitous choices, the total energy flux is conserved, including instantaneous measurements through the shock layer. The dominant incident proton ram energy is converted primarily into downstream proton enthalpy flux, the majority of which is actually carried by a small fraction of suprathermal protons. Fluctuations include both real and instrumental effects. Separating these, resolving the solar wind beam, and other considerations point the way to a dedicated mission to solve this energy partition problem across a full range of plasma and shock conditions. Plain Language Summary: Explosions and fast flows in astrophysical environments lead to the formation of shock waves, the role of which is to process the energy incident upon them. In most astrophysical plasmas, the densities are so low that particle collisions are negligibly rare. Such plasmas are incapable of establishing an equilibrium at a constant temperature across electron and ion species. Astrophysical shocks therefore channel some of that incident energy, for example, to accelerate high‐energy cosmic rays and otherwise partition the energy amongst the plasma's many constituents. This paper addresses, from a holistic approach, this partition problem by employing a mathematical framework to analyze data from state of the art spacecraft that traverse shock waves in interplanetary space. We successfully verify, with some assumptions, overall energy conservation. We also identify sub‐portions and features of the proton population that receive a disproportionate share of the incident energy. The approach naturally highlights the critical measurements and reveals the limitations of using some instruments in regimes for which they were not designed. A dedicated satellite mission to study shock physics would overcome these difficulties. Key Points: We establish and apply a framework to quantify total energy partition across collisionless shocks The fragmented suprathermal ions at the shock and downstream dominate the energy budget Present instrument limitations suggest a roadmap for next generation shock‐dedicated space missions